Efficacy of laser photobiomodulation pulpotomy in human primary teeth: A randomized controlled trial - Chandrashekar Murugesh Yavagal; Akshaya Lal; Viplavi Vijaysinh Chavan Patil; Puja C Yavagal; Kiran Kumar Neelakantappa; Madhu Hariharan (Wolters Kluwer Medknow Publications, 2021)
Background: Laser photobiomodulation (LPBM), also called Low Level Laser Therapy (LLLT), has shown potential to reduce the pulpal inflammation and to preserve the dental pulp vitality, thereby improving healing. Lasers being minimally invasive, safe, and patient friendly prompt its application in pediatric dentistry. Aim: The aim of this study was to evaluate and compare the clinical and radiographic success rates of LPBM and formocresol pulpotomy at 9 months post intervention in human primary molars. Materials and Methods: A randomized controlled, split-mouth study design was followed involving children aged 4-7 years with at least two primary molars indicated for pulpotomy. Sixty-eight eligible primary molars were randomly allocated to two interventions - formocresol pulpotomy (Group I) and LPBM pulpotomy (Group II). Statistical Analyses: Chi-square test was used for statistical analysis fixing significance level at P ≤ 0.05. Results: There was no statistically significant difference in the clinical success rates between the formocresol group (97.05%) and the photobiomodulation group (94.1%) (χ2 = 0.34, P = 0.55); however, the radiographic success rate was significantly high in the laser group (94.1%) compared to the formocresol group (58.82%) (χ2 = 11.76, P = 0.001). Conclusion: LPBM could be a viable nonpharmaceutical alternative for formocresol pulpotomy in human primary teeth